Cetuximab Reconstitutes Pro-Inflammatory Cytokine Secretions and Tumor-Infiltrating Capabilities of sMICA-Inhibited NK Cells in HNSCC Tumor Spheroids - Klöss, Stephan; Chambron, Nicole; Gardlowski, Tanja; Weil, Sandra; Koch, Joachim; Esser, Ruth; Pogge von Strandmann, Elke; Morgan, Michael A.; Arseniev, Lubomir; Seitz, Oliver; Köhl, Ulrike (Frontiers in Immunology, 2015)
Immunosuppressive factors, such as soluble major histocompatibility complex class I chain-related peptide A (sMICA) and transforming growth factor beta 1 (TGF-beta1), are involved in tumour immune escape mechanisms (TIEMs) exhibited by head and neck squamous cell carcinomas (HNSCCs) and may represent opportunities for therapeutic intervention. In order to overcome TIEMs, we investigated the antibody-dependent cellular cytotoxicity (ADCC), cytokine release and retargeted tumour-infiltration of sMICA-inhibited patient NK cells expressing Fcγ receptor IIIa (FcγRIIIa, CD16a) in the presence of cetuximab, an anti-EGFR (epidermal growth factor receptor, HER1) monoclonal antibody (mAb). Compared to healthy controls, relapsed HNSCC patients (n = 5) not currently in treatment revealed decreased levels of circulating regulatory NK cell subsets in relation to increased cytotoxic NK cell subpopulations. Elevated sMICA and TGF-beta1 plasma levels correlated with diminished TNFalpha and IFN-gamma release and decreased NKG2D (natural killer group 2 member D)-dependent killing of HNSCC cells by NK cells. Incubation of IL-2-activated patient NK cells with patient plasma containing elevated sMICA or sMICA analogues (shed MICA [shMICA], recombinant MICA [rMICA]) significantly impaired NKG2D-mediated killing by down-regulation of NKG2D surface expression. Of note, CD16 surface expression levels, pro-apoptotic and activation markers, and viability of patient and healthy donor NK cell subpopulations were not affected by this treatment. Accordingly, cetuximab restored killing activity of sMICA-inhibited patient NK cells against cetuximab-coated primary HNSCC cells via ADCC in a dose-dependent manner. Rapid reconstitution of anti-tumour recognition and enhanced tumour-infiltration of treated NK cells was monitored by 24 h co-incubation of HNSCC tumour spheroids with cetuximab (1 µg/ml) and was characterised by increased IFN-gamma and TNFalpha secretion. This data show that the impaired NK cell-dependent tumour-surveillance in relapsed HNSCC patients could be reversed by the re-establishment of ADCC-mediated effector cell activity, thus supporting NK cell-based immunotherapy in combination with antineoplastic monoclonal mAbs.